1991
DOI: 10.1128/jcm.29.6.1211-1214.1991
|View full text |Cite
|
Sign up to set email alerts
|

Effect of delays in processing on the survival of Mycobacterium avium-M. intracellulare in the isolator blood culture system

Abstract: Concentrations of Mycobacterium avium-M. intracellulare ranging from 10-1 to 163 CFU/ml were added to blood, placed in Isolator tubes, and held at room temperature for intervals ranging from 4 h to 56 days before being processed (centrifugation and culture on Middlebrook 7H10 agar). At all concentrations tested, M. avium-M. intracellulare was recovered after hold times ranging from 4 h to 7 days; the number of final CFU actually increased progressively for hold times of 8 h or more. Hold times of up to 7 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Therefore, lysis of the blood cells by a commercial lysis-centrifugation method (Isolator; Wampole Laboratories, Cranbury, N.J.) or treatment of the blood with a lytic agent such as sodium deoxycholate significantly improves the detection of mycobacteria in blood (171,280,504). Using blood inoculated with known concentrations of mycobacteria, von Reyn et al (464) demonstrated that MAC isolates remain viable in Isolator tubes for at least 7 days.…”
Section: Laboratory Diagnosis Isolation and Identificationmentioning
confidence: 99%
“…Therefore, lysis of the blood cells by a commercial lysis-centrifugation method (Isolator; Wampole Laboratories, Cranbury, N.J.) or treatment of the blood with a lytic agent such as sodium deoxycholate significantly improves the detection of mycobacteria in blood (171,280,504). Using blood inoculated with known concentrations of mycobacteria, von Reyn et al (464) demonstrated that MAC isolates remain viable in Isolator tubes for at least 7 days.…”
Section: Laboratory Diagnosis Isolation and Identificationmentioning
confidence: 99%